Obelia bidentata Clark 1875 - Galea, Horia R.; Schories, Dirk (Zenodo, 2012)
Obelia bidentata Clark, 1875 Material examined . Stn. RAS — 12.ii.2010, Ant.08/2010 (10–40 m): a few, small (2–5 mm high), sterile stems, on bryozoan and basal part of stems of Sertularella gaudichaudi . Geographical distribution . Possibly cosmopolitan; Antarctic records summarized by Peña Cantero (2008). Published as part of Galea, Horia R. & Schories, Dirk, 2012, Some hydrozoans (Cnidaria) from King George Island, Antarctica, pp. 1-21 in Zootaxa 3321 on page 16, DOI: 10.5281/zenodo.213236